Comment on Kluckow M. Barriers to the Implementation of Newborn Pulse Oximetry Screening: A Different Perspective. Int. J. Neonatal Screen. 2018, 4(1), 4 - Thomas L. Gentles; Elza Cloete; Mats Mellander (MDPI AG, 2018)
We read the review article by Kluckow M (Barriers to the Implementation of Newborn Pulse Oximetry Screening[...]